Analisis Kebutuhan Terhadap Pengembangan Program Studi S1 PGMI Pada Masyarakat Islam Kepulauan di Kota Ternate - Nurjannah Nurjannah; Sudin Yamani (Jurnal Ilmiah Wahana Pendidikan, 2023)
A quality educational institution is the dream of all levels of society because it will give birth to quality human beings who are able to bring big changes to the nation. The world of education is currently faced with the challenges of the progress of the times. With the progress of this era, many aspects of life have changed and shifted. Therefore, like it or not, the educational paradigm and system must be adapted to the demands of the times. Of course these changes are expected to lead to a better future education IAIN Ternate is one of the leading State Islamic Universities in the city of Ternate, while the PGMI Undergraduate study program at IAIN Ternate was held in 2014. With the presence of the PGMI Undergraduate Study Program promises great hopes for stakeholders and the archipelagic Islamic community in the City of Ternate. In the effort to develop the PGMI Undergraduate study program, seeing the challenges of the world of work or the level of existing needs, graduates of the PGMI Undergraduate Program are really needed. Therefore, in order to be able to analyze the level of need, it is necessary to obtain accurate information from all parties about the prospects for developing the PGMI undergraduate study program, especially in the island Islamic community in the city of Ternate. This research is a qualitative research, which tries to describe the results of research that the authors found in the field, while the research technique uses interview, observation, and documentation techniques. With data analysis techniques using induction and comparison techniques. Based on the research findings, it can be concluded that: The process of developing the Ternate PGMI FTIK IAIN Ternate undergraduate study program for the Archipelagic Islamic community in Ternate City is carried out through several aspects, as follows: Development of aspects of education and teaching, research and service to the Archipelago Islamic community, Development of aspects cooperation, developing aspects of the quality of learning, developing aspects of the quality of human resources, and developing aspects of study program facilities and infrastructure